A Review of Psychosocial Risk Factors for Pediatric Atopy. (5th March 2012) - Duncan, Christina L.; Simon, Stacey L.
Abstract : Pediatric atopy is increasing in prevalence and creates a significant financial and quality of life burden for children and families (e.g., frequent clinic visits, academic, and social challenges). Thus, it is important to understand modifiable risk factors related to disease onset or exacerbation in young children. The existing research base suggests that while a genetic link has been identified, specific family psychological factors (e.g., parent stress) also appear to play a significant role in the development of pediatric atopy. The function of psychological stress in the clinical expression and exacerbation of allergic diseases in young children is hypothesized to be due to neuroendocrine and immunologic systems. Specifically, stress-related activation of the sympathetic and adrenomedullary (SAM) system as well as the hypothalamic-pituitary-adrenocortical (HPA) axis from both the intrauterine environment and early childhood experiences may increase risk of childhood atopy above and beyond genetic risk. Consequently, prevention and intervention strategies aimed at reducing children's early exposure to stress and psychological difficulties in parents may prove beneficial in preventing or reducing the likelihood that their children will develop atopy.